Analysis of corporate social disclosure practices in annual reports: an experience with the private commercial banking sector of Bangladesh - Rahman, Sharmin Shabnam (International Journal of Research in Computer Application and Management, 2016)
This article was published in International Journal of Research in Computer Application and Management [© 2013 International Journal of Research in Computer Application and Management] and the definite version is available at : http://ijrcm.org.in/article_info.php?article_id=3730 The article website is at:http://ijrcm.org.in/comapp/